The martyrdom of Nurse Cavell : The life story of the victim of Germany's most barbarous crime - Hill, William Thomson, 1875- (Salt Lake City, UT : Project Gutenberg, 2022)
"The Martyrdom of Nurse Cavell" by William Thomson Hill is a historical account written in the early 20th century. The book chronicles the life and tragic execution of Edith Cavell, a British nurse who is remembered for her bravery and compassion during World War I. It explores themes of patriotism, sacrifice, and the struggle for humanity amidst the horrors of war. In this poignant narrative, the author details Cavell's upbringing, her dedication to nursing, and her commitment to helping wounded soldiers, regardless of their nationality. The story unfolds in Brussels during the German occupation, where her acts of compassion ultimately lead to her arrest by the German authorities. Despite a lack of evidence for espionage, she is tried in a secret court-martial and sentenced to death, which is carried out swiftly and cruelly. Hill illustrates not just Cavell's personal courage and the moral dilemmas she faced, but also the widespread outrage her execution incited, galvanizing support for the war effort in Britain and beyond. (This is an automatically generated summary.)
Release date is 2022-05-22
Tim Lindell and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Cavell, Edith, 1865-1915; Nurses -- Biography